Competition and Cooperation in Divisible Good Auctions: An Experimental Examination - Sade, Orly; Schnitzlein, Charles; Zender, Jaime F. (Review of Financial Studies, 2006)
An experimental approach is used to examine the performance of three different multiunit auction designs: discriminatory, uniform-price with fixed supply, and uniform-price with endogenous supply. We find the actual strategies to be inconsistent with theoretically identified equilibrium strategies. The discriminatory auction is found to be more susceptible to collusion than either uniform-price auction and so, contrary to theoretical predictions and previous experimental results, it generates the lowest average revenue. Consistent with theoretical predictions, the actual bid schedules are more elastic with reducible supply or discriminatory pricing than in the uniform-price auction with fixed supply.